2016
DOI: 10.1177/0309133315624642
|View full text |Cite
|
Sign up to set email alerts
|

Rule-based analysis of throughfall kinetic energy to evaluate biotic and abiotic factor thresholds to mitigate erosive power

Abstract: Below vegetation, throughfall kinetic energy (TKE) is an important factor to express the potential of rainfall to detach soil particles and thus for predicting soil erosion rates. TKE is affected by many biotic (e.g. tree height, leaf area index) and abiotic (e.g. throughfall amount) factors because of changes in rain drop size and velocity. However, studies modelling TKE with a high number of those factors are lacking. This study presents a new approach to model TKE. We used 20 biotic and abiotic factors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…However, for the relation of LAI and TKE inconsistent findings are described in previous studies. For example, Nanko et al () and Geißler et al () found a negative influence of LAI on TKE below trees larger than 15 m. Goebes et al () in contrast, found a positive correlation of LAI and TKE in an early‐successional forest plantation. These differences might result from differences in the vertical distribution of the leaf area, especially due to varying vegetation heights.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the relation of LAI and TKE inconsistent findings are described in previous studies. For example, Nanko et al () and Geißler et al () found a negative influence of LAI on TKE below trees larger than 15 m. Goebes et al () in contrast, found a positive correlation of LAI and TKE in an early‐successional forest plantation. These differences might result from differences in the vertical distribution of the leaf area, especially due to varying vegetation heights.…”
Section: Methodsmentioning
confidence: 99%
“…The crown base height (CBH) can be seen as ‘the last barrier' of the canopy (Goebes et al, ) determining the lowest falling height of drips. Although, CBH is found to be rather influential on TKE (Nanko et al, ; Goebes et al, ) it does not represent the whole vegetation: The presence of shrubs and other vegetation below the crown lead to re‐interception.…”
Section: Methodsmentioning
confidence: 99%
“…This finding was later substantiated by others (e.g., Refs 9,11,19,43,and 57). Readers specifically interested in throughfall DSD and throughfall kinetic energy in relation to soil erosion are referred to Nanko et al, 21 Geißler et al, 24 and Goebes et al, 58 among others whose calculations of throughfall kinetic energy assume that the fall height of release throughfall is equal to the canopy height from which the droplets detach. 20,50,52,[59][60][61] In addition to its application to soil erosion studies, throughfall DSD is useful to estimate canopy interception loss.…”
Section: Characteristics Prediction and Usage Of Throughfall Drop Size Distributionmentioning
confidence: 99%
“…In this context, soils inhere ecosystem functions that have direct impact on human societies (Berendse et al, 2015). Examples of these soil functions include water purification by filtration, food production by forming a support system for plants, stabilizing climate change by carbon sequestration and the provision of a physical basis for human activities (Keesstra et al, 2012;Goebes et al, 2015). However, soil erosion and the accompanied loss of topsoil result in soil quality degradation, and therefore in a declining capacity of soils to provide the ecosystem functions (Lal, 2003;Morgan, 2005;Boardman, 2006).…”
Section: Introductionmentioning
confidence: 99%